Pengaruh Pengalaman Konsumen dan Kepuasan Konsumen terhadap Niat Beli Ulang pada Pembelian Produkskincare di E-Commerce Shopee - Agustina Agustina; Djati Julitriarsa (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
One way to rapidly develop the current buying and selling business is to sell products online, both from social media and on e-commerce trading platforms. The development of e-commerce in Indonesia is currently so fast, this is influenced by the increasing number of internet users. The consumer experience begins when the consumer sees a promotion about a product or service until finally the consumer decides to buy a product or use a service. If consumers are satisfied with the service or experience they get from a product, it is likely that consumers will make repeat purchases. In this study the authors use quantitative research with descriptive methods because the data obtained will be processed quantitatively. The results of this study are in accordance with the first hypothesis, the t value of X1 is 2,920 > t table 1,983 and a significant value (Sig) 0.004 < 0.05, it can be stated that the consumer experience variable has a significant positive effect on repurchase interest in purchasing skincare products at e-commerce shopee. . From the results of the second hypothesis test, the t-count value is 4.809 > t table 1.983 and a significant value (Sig) 0.000 <0.05, it can be stated that consumer satisfaction has a significant positive effect on repurchase intention.